Association between TNF-a promoter -308G/A polymorphism and essential hypertension in the Asian population: A meta-analysis - Yao, Ying-shui (J Renin Angiotensin Aldosterone Syst, 2017)
OBJECTIVE: The results of studies on the association between tumor necrosis factor-a -308G/A (TNF-a -308G/A) polymorphism, and susceptibility to essential hypertension are controversial. To derive a more precise estimation, we conducted a meta-analysis of all similar articles. METHODS: The summary effect odds ratios and 95% confidence intervals were obtained. Funnel plots and Egger’s test were used to estimate publication bias, and heterogeneity was assessed by the chi-square-based Q-test and I(2) test. RESULTS: Nine studies (with 1437 cases and 1487 controls) were included. In the overall analysis, the combined results showed that there were significant differences in genotype distribution between essential hypertension cases and controls, AA+GA versus GG (OR = 1.53, 95% CI: 1.25–1.88, p < 0.00001). In the stratified analysis by country, we found that essential hypertension cases had a significantly higher frequency of AA+GA versus GG (OR = 1.47, 95% CI: 1.18–1.81, p = 0.0004) than control in the Asian population. CONCLUSIONS: This meta-analysis supports previous findings that TNF-a -308G/A polymorphism may increase the risk of essential hypertension, at least in the Asian population.